Folklore and Local Culture Analysis in Local Product Marketing: Strategies for Global Business - Asrofi, Imam; Sholehah, Mar'atus Nur (International Journal of Language and Culture, 2023)
The problem raised in this study is the challenge local products face in entering an increasingly competitive global market, particularly in integrating local culture and folklore into product marketing strategies. The use of local cultural elements has the potential to be a strong differentiation tool, but it often encounters obstacles in terms of artistic sensitivity and international market acceptance. This research aims to analyze how local culture and folklore can be applied in local product marketing to compete in the global market, as well as to identify the challenges and opportunities companies face in integrating local culture into their marketing strategies. This study employs a literature review approach, where various relevant sources are collected and analyzed to understand the application of local culture in product marketing and explore related challenges and opportunities. The findings of this study indicate that integrating local culture into product marketing can enhance product appeal in the global market, increase consumer loyalty, and build stronger emotional connections with international consumers. However, achieving this success requires in-depth market research and a culturally sensitive approach to avoid miscommunication or cultural distortion.